Tobacco Cessation May Improve Lung Cancer Patient Survival. Issue 7 (July 2015) - Dobson Amato, Katharine A.; Hyland, Andrew; Reed, Robert; Mahoney, Martin C.; Marshall, James; Giovino, Gary; Bansal-Travers, Maansi; Ochs-Balcom, Heather M.; Zevon, Michael A.; Cummings, K. Michael; Nwogu, Chukwumere; Singh, Anurag K.; et al.
Abstract : Introduction: This study characterizes tobacco cessation patterns and the association of cessation with survival among lung cancer patients at Roswell Park Cancer Institute: an NCI Designated Comprehensive Cancer Center. Methods: Lung cancer patients presenting at this institution were screened with a standardized tobacco assessment, and those who had used tobacco within the past 30 days were automatically referred to a telephone-based cessation service. Demographic, clinical information, and self-reported tobacco use at last contact were obtained via electronic medical records and the Roswell Park Cancer Institute tumor registry for all lung cancer patients referred to the service between October 2010 and October 2012. Descriptive statistics and Cox proportional hazards models were used to assess whether tobacco cessation and other factors were associated with lung cancer survival through May 2014. Results: Calls were attempted to 313 of 388 lung cancer patients referred to the cessation service. Eighty percent of patients (250 of 313) were successfully contacted and participated in at least one telephone-based cessation call; 40.8% (102 of 250) of persons contacted reported having quit at the last contact. After controlling for age, pack year history, sex, Eastern Cooperative Oncology Group performance status, time between diagnosis and last contact, tumor histology, and clinical stage, a statistically significant increase in survival was associated with quitting compared with continued tobacco use at last contact (HR = 1.79; 95% confidence interval: 1.14–2.82) with a median 9 month improvement in overall survival. Conclusions: Tobacco cessation among lung cancer patients after diagnosis may increase overall survival.